Design and production of educational material on causes and means of control of air pollution - Del Carpio Gallegos, Javier (2001)
Educational programs on causes and means of controlling atmospheric pollution'seek to inform, educate, instruct and strengthen public participation in all aspects related with health and air quality, as well as with prevention and reduction of air pollution. To achieve this result, two necessary instruments have been designed: a primer pad and a virtual book about atmospheric pollution. This will promote decision making on the importance of prevention and reduction of air pollution in the city.